2019
DOI: 10.3390/medicina55060235
|View full text |Cite
|
Sign up to set email alerts
|

Severe Abnormalities of Lens Epithelial Cells in Exfoliation Syndrome: A Transmission Electron Microscopy Study of Patients with Age-Related Cataract

Abstract: Background and objectives: The aim of this study was to examine via electron microscopy the lens epithelial cells in age-related cataracts and compare the findings between patients with and without exfoliation syndrome, in the Greek population. Materials and Methods: Twenty-one patients with age-related cataracts, older than 60 years, were included in the study. Eleven of them also suffered from exfoliation syndrome. Anterior lens capsules, obtained during phacoemulsification, were examined with a transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 41 publications
1
16
0
4
Order By: Relevance
“…TEM examination revealed similar findings to our previous studies [14, 16]. An unbound, electron-dense, microgranular, spherical material was recorded in 3 out of 7 XFS aLCs (Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…TEM examination revealed similar findings to our previous studies [14, 16]. An unbound, electron-dense, microgranular, spherical material was recorded in 3 out of 7 XFS aLCs (Fig.…”
Section: Resultssupporting
confidence: 90%
“…We recently studied aLCs of XFS patients with transmission electron microscopy (TEM) for the first time in a Greek population. We have already reported novel TEM observations such as severe abnormalities of the lens epithelial cells (LECs) [14], the presence of exfoliation fibrils within the basement membrane of the aLC [15], and the presence of a new, not previously described material on the apical side of the lens epithelium, towards the lens fibers [16]. It is mainly the latter ultrastructural alterations that seem to be related to easier hydrodissection in XFS patients, as described lately [17].…”
Section: Introductionmentioning
confidence: 99%
“…It was this observation that stimulated our recent transmission electron microscopy studies of anterior lens capsules in XFS. Transmission electron microscopic examination revealed severe abnormalities of lens epithelial cells [13], the presence of exfoliation fibrils within the basement membrane of the anterior lens capsule [18], and the presence of new, not previously described material on the apical side of the lens epithelium towards the lens fibers [12]. The lens epithelial surface exhibited a highly irregular margin, with extracellular material covering the lens epithelial cells' apical membrane in exfoliation patients.…”
Section: Discussionmentioning
confidence: 89%
“…Recent electron microscopy studies of the anterior lens capsule in patients with XFS have revealed newly described ultrastructural alterations of the lens epithelium and its apical surface towards the lens fibers, indicating a disorder of the lens's epithelial-fiber interface in XFS [12,13]. To our knowledge, there has been no report or any kind of evaluation of difficulties with hydrodissection among patients with cataract, including those with XFS.…”
Section: Introductionmentioning
confidence: 95%
“…In electron microscopy observation, the LECs’ flattening seems to be related to cataract degenerative manifestations, which constitute a quite common finding [ 6 ]. However, LECs’ destruction is not usually described ultrastructurally and, in this case, is probably attributed to the mechanical friction caused by lens rupture.…”
Section: Discussionmentioning
confidence: 99%